Analysis of layering-related linear features on comet 67P/Churyumov–Gerasimenko. Issue 4 (13th November 2018) - Ruzicka, Birko-Katarina; Penasa, Luca; Boehnhardt, Hermann; Pack, Andreas; Dolives, Benoit; Souvannavong, Fabrice; Remetean, Emile
ABSTRACT: We analysed layering-related linear features on the surface of comet 67P/Churyumov–Gerasimenko (67P) to determine the internal configuration of the layerings within the nucleus. We used high-resolution images from the OSIRIS Narrow Angle Camera onboard the Rosetta spacecraft, projected on to the SHAP7 shape model of the nucleus, to map 171 layering-related linear features which we believe to represent terrace margins and strata heads. From these curved lineaments, extending laterally to up to 1925 m, we extrapolated the subsurface layering planes and their normals. We furthermore fitted the lineaments with concentric ellipsoidal shells, which we compared to the established shell model based on planar terrace features. Our analysis confirms that the layerings on the comet's two lobes are independent from each other. Our data are not compatible with 67P's lobes representing fragments of a much larger layered body. The geometry we determined for the layerings on both lobes supports a concentrically layered, 'onion-shell' inner structure of the nucleus. For the big lobe, our results are in close agreement with the established model of a largely undisturbed, regular, concentric inner structure following a generally ellipsoidal configuration. For the small lobe, the parameters of our ellipsoidal shells differ significantly from the established model, suggesting that the internal structure of the small lobe cannot be unambiguously modelled by regular, concentric ellipsoids and could have suffered deformational or evolutional influences. A more complex model is required to represent the actual geometry of the layerings in the small lobe.